2007
DOI: 10.1080/09638280601129231
|View full text |Cite
|
Sign up to set email alerts
|

Injury among 1107 Canadian students with self-identified disabilities

Abstract: Canadian students who report disabilities experience higher risks for injury than their peers, perhaps due to an inability to perceive and avoid environmental hazards. Injury prevention programmes are needed to address these unique risk profiles in order to prevent additional disability or secondary conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(34 reference statements)
2
6
0
Order By: Relevance
“…A similar association was reported among children with intellectual disability in Australia [22]. Our results also confirm the previous work that reported injury risk difference by disability types [1820,33]. Although previous studies reported a dose-response association between disability severity and injury risk in adults with disabilities [34,35],we did not find a clear dose-response relationship in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A similar association was reported among children with intellectual disability in Australia [22]. Our results also confirm the previous work that reported injury risk difference by disability types [1820,33]. Although previous studies reported a dose-response association between disability severity and injury risk in adults with disabilities [34,35],we did not find a clear dose-response relationship in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of the U.S. National Health Interview Survey data found that children with disability were at a significant higher risk of injuries than children without disability [19]. A study from Canada reported a 30% increases in the risk of injury in children with disabilities compared with their healthy peers [20]. Ramirez et al reported that children with disabilities had over twice the school injury rate of children without disability [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that a low exposure to physical activities shows low levels of sports related injuries (Raman et al 2007), and in our study, approximately half of adolescents with affected LTID were likely to report their main injury to have taken place during sports. Adolescents with affected LTID may have functional difficulties, learning difficulties or chronic conditions that affect their participation and these elevated risks of injuries may be from serious non-sports related events.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, adolescents who reported more LTID conditions were at even greater risks of medically attended injuries (Raman et al 2007). Numerous studies have reported the higher threat of sports related injuries among adolescents with LTID than the general participation (Shi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research overseas has documented increased risk particularly relating to falls,5 10 burns,6 motor vehicles7 and assaults 9 31. Previous research often included preschool and primary school children in their study populations,5–10 24 32 and some studies focused on specific types of disability32 or injury 6 7…”
Section: Discussionmentioning
confidence: 99%